m-39=-11

Simple and best practice solution for m-39=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-39=-11 equation:


Simplifying
m + -39 = -11

Reorder the terms:
-39 + m = -11

Solving
-39 + m = -11

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '39' to each side of the equation.
-39 + 39 + m = -11 + 39

Combine like terms: -39 + 39 = 0
0 + m = -11 + 39
m = -11 + 39

Combine like terms: -11 + 39 = 28
m = 28

Simplifying
m = 28

See similar equations:

| 7r^2-4r+7=0 | | y=-3(3)+5 | | 40a^3+5b^3= | | -3y-15=45 | | 7x+3(x-2)=6(x+1)-3 | | 2(k+5)-3=k+18 | | Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 |

Equations solver categories